2022
DOI: 10.1161/circep.122.011145
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for Early Pacemaker Implantation in Patients With Postoperative Heart Block After Congenital Heart Surgery

Abstract: BACKGROUND: Guidelines recommend observation for atrioventricular node recovery until postoperative days (POD) 7 to 10 before permanent pacemaker placement (PPM) in patients with heart block after congenital cardiac surgery. To aid in surgical decision-making for early PPM, we established criteria to identify patients at high risk of requiring PPM. METHODS: We reviewed all cases of second degree and complete heart block (CHB) on POD 0 from August 2009 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…CHB was found to be the most common cause of PPI (55.2%), followed by SSS (22.3%) and other arrhythmias. These findings are consistent with previous research 14 that reported that patients with postoperative CHB can accurately be identified to undergo permanent pacemaker placement, emphasizing the critical significance of conduction system abnormalities in necessitating pacemaker intervention. The incidence of CHB and SSS emphasizes the therapeutic need for early detection and intervention to improve patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CHB was found to be the most common cause of PPI (55.2%), followed by SSS (22.3%) and other arrhythmias. These findings are consistent with previous research 14 that reported that patients with postoperative CHB can accurately be identified to undergo permanent pacemaker placement, emphasizing the critical significance of conduction system abnormalities in necessitating pacemaker intervention. The incidence of CHB and SSS emphasizes the therapeutic need for early detection and intervention to improve patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of CHB and SSS emphasizes the therapeutic need for early detection and intervention to improve patient outcomes. 14 …”
Section: Discussionmentioning
confidence: 99%
“…These findings support the notion that the underlying causes of conduction system defects differ between these age groups of patients. Post-operative heart block following the surgical correction or repair of congenital heart disease has been well described (19)(20)(21)(22). In our study population, three patients with congenital heart disease had immediate post-operative heart block which did not revert back to their pre-operative rhythm requiring permanent pacemaker implantation during their time of admission.…”
Section: Discussionmentioning
confidence: 87%
“…Continuing with the 2.5% in the MVR group of our study, 1.8% [ 3 ], 4.5% [ 27 ], 7.6% [ 23 ], and 8.2% were disclosed by other related evidence. PPI prevalence in the congenital heart surgery group was 0.72% compared to a prevalence rate of 1% [ 28 , 29 ] in recent studies. Moreover, the expected time between surgery and PPI was 11 days, which is in line with previous studies [ 1 , 3 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 93%